Development and characterization of sugar palm (Arenga pinnata (Wurmb) Merr.) nanocellulose/thermoplastic starch/poly (lactic acid) biocomposites - Asmawi, Nazrin Nurarief Mardi (2022)
In recent years, the escalating of petroleum-based plastic wastes had urged researchers to develop alternative biodegradable packaging plastics derived from bioresources. Traditional plastics are non-biodegradable associated with environment pollutions endangering human and animal life. In this study, sugar palm crystalline nanocellulose (SPCNC) reinforced thermoplastic sugar palm starch (TPS)/poly (lactic acid) (PLA) blend biocomposites were prepared using melt blending and compression moulding. Prior to melt blending process, the dispersion of SPCNC at a fixed loading (0.5%) within TPS was achieved via sonication which later proceed with solution casting method to produce TPS biocomposite films. The PLA and TPS were blended into 5 different ratios (PLA/TPS; 20:80, 40:60, 60:40, 70:30, 80:20) using Brabender mixer. The effectiveness of SPCNC reinforcement based on the compatibility of each composition was evaluated using scanning electron microscopic (SEM) analysis, Fourier transform infrared spectroscopy (FTIR), thermal gravimetric analysis (TGA), X-ray diffraction (XRD) analysis, dynamic mechanical analysis (DMA), limiting oxygen index (LOI), tensile, flexural, impact strength, thickness swelling, water solubility, water absorption, water vapour permeability, flammability, soil and aqueous environment biodegradation test. XRD patterns of all blends biocomposite samples elucidate amorphous scattering background due to the obstruction of PLA side groups to form hydrogen bond between starch molecule chains. Among all samples, PLA40TPS60 and PLA60TPS40 had the good compatibility as indicated by the minor agglomeration and crack lines through SEM images. FTIR spectra exhibited lower wavenumber shift in the O–H band compared to other samples. Thickness swelling recorded minor reduction from PLA40TPS60 (11.41%) to PLA60TPS40 (10.72%). Both samples were classified as HB in UL94 rating flammability test with PLA40TPS60 (19.2%) had slightly higher LOI value compared to PLA60TPS40 (18.8%). The PLA40TPS60 had the highest improvement in tensile, flexural and impact strength, which are 75.47%, 72.63% and 33.13% respectively. At PLA60TPS40, the tensile, flexural and impact strength were improved by 20.89%, 25.20% and 12.09% respectively. DMA results showed a significant increment in storage modulus (E′) for PLA60TPS40 (53.2%) compared to the trivial changes of PLA70TPS30 (10%) and PLA80TPS20 (0.6%). The PLA60TPS40 demonstrated a higher degradation temperature at 25% (307 °C) and 50% (324 °C) weight losses compared to PLA70TPS30. The water vapour permeability was reduced up to 1.02×10−11 g/m.s.Pa for PLA60TPS40 but increased at PLA70TPS30 (1.1×10−11 g /m.s.Pa). For the PLA60TPS40, significant reduction (46% – 69%) was recorded in maximum water uptake in all mediums while soil degradation rate experienced insignificant increment (7.92%). The PLA60TPS40 indicated water solubility value of 39.43% corresponded to the proportion of TPS content. PLA60TPS40 displayed well dispersed TPS within PLA phase correspondingly to SPCNC distribution resulting insignificant reduction in mechanical, water barrier and thermal properties. In effort to overcome plastics pollution and reduce the over-reliance on depleting fossil resources, biodegradability and low-cost material are prioritized rather than maximizing their functional properties.